Lamp with the image of the Greco-Egyptian god Sarapis from Deultum (Research Announcements "Heritage BG", 2025)
During excavations in 2009 in the ancient Roman colony of Deultum archaeologists came across a ceramic lamp with an atypical forthe regionimage and dated to the 2-3rd century AD. It is undoubtedly an extremelyintriguing monument that fits into a familiar but very rare category of objects with probable Egyptian origin. The image on it represents a garlanded cultic statue of the Greco-Egyptian god Sarapis perceived as savior and cosmocrator from the Roman Emperors. It probably marks a ceremonial procession during a well-known festival associated with the Nile flood. The ceremonial statue of Sarapis is accompanied also by two cobras with crowns which are the syncretic deities Isis-Thermutis and Sarapis-Agathodemon. Their role was certainly to to protect the cultic image of the God but also to complete the Egyptian character of the whole scene. References:Atanassova, V. (2019). Egipetskite bojestva Izida i Sarapis v Serdica. – Thracia 24, 418–434.Beaud, R. (1990). L’offrande du collier-ousekh. In: Studies in Egyptology Presented to Miriam Lichtheim, I (ed. S. Israelit-Groll). Jérusalem, 46–62.Bricault, L. (2020). Les cultes isiaques dans le monde gréco-romain. In: Les cultes isiaques Serdica (eds. Vessela Atanassova, Laurent Bricault). Sofia: Paradigma, 14–33.Deschênes, G. (1980). Isis-Thermouthis: exemple d’un biculturalisme. In: Mèlanges d’ètudes anciennes offerts a Maurice Lebel (eds. Jean-Benoit Caron, Michel Fortin, Gilles Maloney). Queìbec, 363–370.Dunand, F. (1969). Les représentations de l’agathodeimon. À propos de quelques bas-reliefs du museìe d’Alexandrie. – Bulletin de l’Institut français d’archéologie orientale 67, 9–48.Dunand, F. (1981). Agathodaimon. In: Lexicon Iconographicum Mythologiae Classicae I. Zürich, 277–282.Kobylina, M. M. (1976). Divinités orientales sur le littoral nord de la mer Noire. Études préliminaires aux religions orientales dans l’Empire romain 52.Leclant, J., & Clerc, G. (1994). Osiris Kanopos. In: Lexicon Iconographicum Mythologiae Classicae VII/1. Bern, 129–130.Malaise, M. (2009). Le calathos de Sérapis. – Studien zur Altägyptischen Kultur 38, 173–193.Malaise, M. (2009a). Le basileion, une couronne d’Isis: origine et signification. In: Elkab and beyond. Studies in honour of Luc Limme (eds. Wouter Claes, Stan Hendrickx, Herman de Meulenaere). (Orientalia Lovaniensia Analecta 191). Leuven, 445–461.Pietrzykowski, M. (1978). Sarapis – Agathos Daimon. In: Hommages M. J. Vermaseren (eds. Margreet de Boer, T. A. Edridge). Études préliminaires aux religions orientales dans l’Empire romain 68/3. Leiden, 959–966.Podvin, J. L. (2011). Luminaire et cultes isiaques. (Monographies Instrumentum, 38). Montagnac: Editions Mergoil.Quaegebeur, J. (1975). Le Dieu égyptien Shaï dans la religion et l’onomastique. Leuven University Press.Tran Tam Tinh, V. (1981). Quelques representations insolites de Serapis. In: Mythologie gréco-romaine, mythologies périphériques: études d’iconographie [Colloques internationaux du C.N.R.S., 593] (eds. Lilly Kahil, Christian Augé). Paris, 145–150.Tran Tam Tinh, V. (1983). Sérapis debout: corpus des monuments de Sérapis debout et étude iconographique, Études préliminaires aux religions orientales dans l’Empire romain 94. Leiden.Veymiers, R. (2009). Ἵλεως τῷ φοροῦντι. Sérapis sur les gemmes et les bijoux antiques. Bruxelles: Académie Royale de Belgique.Waldhauer, O. (1914). Kaiserliche Ermitage: die antiken Tonlampen. St-Pétersbourg.Sources:Pseudo-Callisthène, Roman d’Alexandre I, 32, 5-7, 10-13.
Keywords: Thrace; Egypt; Sarapis; Isis-Thermuthis; Sarapis-Agathodaimon; Roman Lamps